(untitled) (Journal of the College of Basic Education, 2022)
Complexes of Zn(II),Cd(II) and Hg(II) with mixed ligands of phenylalanine (L) and tributylphosphine (TBPh) were prepared in aqueous ethanol with (1:2:2) (M:L:TBPh). The prepared complexes were characterized using flame atomic absorption, (C.H.N) Analysis, FT.IR and UV-Vis spectroscopic methods as well as conductivity measurements. From the obtained data the octahedral structure was suggested for all prepared complexes.